The Effect of the Quality of Accessibility and Facilities on the Decision to Visit Gope Beach, Serang-Banten City - Nurlatifah Ismail; Rahmat Ingkadijaya; Sri Mariati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The city of Serang does have a marine beauty that can be taken into account, one of which is the coastal marine tourism area of Gope Karangantu, this beach tourism destination is one of the marine tourism destinations of the Serang city government which is managed by the Karangantu Archipelago Fisheries Port under the Indonesian Ministry of Maritime Affairs and Fisheries, but based on data The results obtained for five years, namely 2016 to 2020, this beach visitor is unstable and even tends to decrease and only in certain months this beach is crowded with visitors. Research Objectives: 1) To determine the effect of Accessibility Quality on the decision to visit Gope Beach tourism object. 2) To determine the effect of facilities on the decision to visit Gope Beach tourism object. 3) To determine the effect of the quality of accessibility and facilities simultaneously on the decision to visit Gope Beach tourist attraction. 4) To determine the most dominant influence among the variables of accessibility, quality and facilities on the decision to visit Gope Beach tourist attraction. This research is a quantitative study using the reliability formula, multicollinearity, multiple correlation, coefficient of determination, multiple linear regression analysis, T test and Y. From the research results, Quality of Accessibility and Facilities simultaneously have a strong influence on the decision to visit Gope Beach tourism objects, the R value is (0.806).